Reproductive toxicity and teratogenicity studies of Kacip fatimah (Labisia pumila) in rats - Sulaiman, Siti Amrah (Pusat Pengajian Sains Kesihatan, Universiti Sains Malaysia, 2009)
Research has been conducted on standardised aqueous extract of Kacip Fatimah or Labisia pumilar (var. alata), commercially known as Biolabisia., on the reproductive, developmental and female toxicity in Sprague Dawley rats. Results obtained indicated that the administration of Biolabisia"' up to 1000 mg/kg/day did not cause mortality nor show noticeably any treatment-related signs of toxicity on the physical appearance and behaviour of all the rats studied. There was a consistent trend of less weight gain noted in all the herbal treated group animals. Treatment with Biolabisia® to pregnant rats did not result in significant foetal loss or any congenital malformations. The duration of oestrous cycles and reproductive organs weight of rats were statistically unaffected by Biolabisia"', however the increase number of rats with irregular cycles, presence of polycystic ovaries and increasing trends in progesterone and free testosterone hormonal levels in animals that received 1000 mg/kg/day Biolabisia., raised a little concern. Taking all the cumulative data together, the current findings suggest that oral treatment of Biolabisia., up to 1000 mg/kg/day in female rats is not associated with significant deleterious effects in reproductive parameters in rats. However, body weight and estrous cycle of the females could be affected if Biolabisia"' is administered at a very high dose and for a longer duration. These could be due to the androgenic effects of the herb in rats.